A Study on Polyherbal Formulation for Kidney Protection: Exploring the nephroprotective and hepatoprotective potential of a polyherbal formulation (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Polyherbal formulations have long been used for liver protection, kidney protection, hepaticdysfunction treatment, and regeneration. They may help enhance appetite and protect the gastrointestinalsystem. The purpose of the current research was to analyse the potential of herbal formulation made up ofWedeliachinensis leaves and Boerhaaviadiffusa roots in having activities like nephroprotectivity andhepatoprotectivity. Nephroprotective and hepatoprotective efficacy was studied using MTT cytotoxicitytest employing mammalian cell culture. The findings of the hepatoprotective and nephroprotectiveactivities demonstrated that the formulation combination of herbs Wedeliachinensis andBoerhaaviadiffusa roots is a great source of organ stimulant with high therapeutical relevance. Thehepatoprotective and nephroprotective qualities make this formulation a unique one concentrating onliver and kidney illnesses.